The elevation of fibroblast growth factor 21 is associated with generalized periodontitis in patients with treated metabolic syndrome - Teerat Sawangpanyangkura; Panwadee Bandhaya; Pattanin Montreekachon; Anongwee Leewananthawet; Arintaya Phrommintikul; Nipon Chattipakorn; Siriporn C. Chattipakorn (BMC, 2022)
Abstract Background Fibroblast growth factor 21 (FGF21) is closely associated with metabolic syndrome (MetS). An alteration of FGF21 is possibly affected by periodontitis. The present study aimed to investigate the levels of serum FGF21 in MetS patients with generalized periodontitis and its association with periodontal and metabolic parameters. Methods One hundred forty-six MetS patients were recruited from the CORE (Cohort Of patients at a high Risk for Cardiovascular Events) Thailand registry. All participants received general data interviewing, periodontal examination and blood collection for measurement of FGF21 levels and biochemistry parameters. Periodontitis was defined according to the new classification and divided into two groups of localized periodontitis and generalized periodontitis. Results FGF21 was significantly higher in generalized periodontitis group when compared with localized periodontitis group (p <  0.05). The significant correlation was observed between FGF21 and variables including number of remaining teeth, mean clinical attachment loss, hypertriglyceridemia and low high-density lipoprotein cholesterol. The elevation of serum FGF21 was associated with presence of generalized periodontitis after adjusting of covariate factors (OR = 27.12, p = 0.012). Conclusions The elevation of serum FGF21 might be a potential biomarker for MetS patients who have risk of generalized periodontitis.